Contribuições da obra de Guacira Lopes Louro para pensar a educação sexual como categoria de formação docente - Barros, Alexsandra Gomes (2023)
The qualitative approach guides the documentary and bibliographical research of this dissertation, allowing the analysis of Guacira Lopes Louro's discourse on Sexual Education as a category of teacher training. The theoretical assumptions of the research cover the classes of post-modernity, post-criticism in education, Foucauldian post-structuralism, cultural studies in education and queer thinking. We collected documentary data from articles, book chapters and books authored by Guacira Lopes Louro, in addition to interviews and lectures given by her. We also consider some normative bases that structure Brazilian education, with emphasis on the initial and continued training of teachers, focusing on sex education as a category. As for the survey of bibliographic data, we compiled it from publications (articles, book chapters and books) by authors who write from Guacira Lopes Louro. The Foucauldian analysis of the research is central to the categories device, discourse, discursive practice, condition of production and modes of subjectivation. Guacira Lopes Louro not only considers it of fundamental importance that the category Sexual Education be an organic part of the initial teacher training curriculum, but also understands that the continuing education processes must take on the theme, given the demands that are pronounced in the school itself, being a question of historical, social, cultural, political and academic relevance, in particular when considering the current outlines and “silences” of Brazilian educational policies on the Sexual Education category. The “silence” becomes even more perverse when the cultural dimension is considered, given the distrust of the naturalization/biologization of straight sexuality. The centrality of the research is the Training of Teachers to work with Sexual Education. This is how we biograph Guacira Lopes Louro and talk about Sexual Education and Teacher Training in the field of Sexual Education. The Technical-Technological Product (PTT) is a pedagogical proposal for teacher training, which, based on problematizations, through cinequeer, provides clues for working with the Sexual Education category in a post-critical bias, as we understand that the heteronormative sexuality pedagogy device and normalizing, through its operations, produces violent, demeaning and systematic subjection to carry out the erasure and subalternization of sexualities qualified as abject, peripheral or abnormal. Problematizing education, with a queer disposition, signals possibilities for education and Sex Education from a citizenship perspectiv